Study of Vibration Pattern Recorded While Turning of EN8 and EN24 using MPU6050 - Joshi, Anurag; Shukla, DD; Goyal, Ravi Kumar (International Journal of Engineering and Technology, 2018)
The need for precise along with optimum measurement and result oriented investigation of mechanical vibration has grown and implemented in various mechanical operations. The method adopted to measure the vibration of a particular piece of machinery is by mounting an accelerometer and measuring the accelerations produced by the vibration. The primary agenda of this work is to assess and study the vibrations generated in the machine while doing machining EN8 and EN24 at different depth of cut. The experiment was performed by mounting a 3-axis accelerometer (MPU-6050) on the tool post of lathe machine (LDLM-02) switched to turning centre. The device was calibrated using Arduino software whose output signals were logged in Microsoft Excel which turned out as desired vibration levels.Â Â  Â